2005
DOI: 10.1159/000089273
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Forward Shift of Posterior Corneal Surface after Operation between LASIK and LASEK

Abstract: Purpose: To compare the forward shift of the posterior corneal surface as a function of time after surgery between successful laser in situ keratomileusis (LASIK) and laser-assisted subepithelial keratectomy (LASEK). Methods: Twenty-two eyes from 14 patients who underwent LASIK and 19 eyes from 10 patients who underwent LASEK were reviewed retrospectively. The uncorrected visual acuity, spherical equivalent and pachymetry were obtained before and 1 or 2 weeks and 2, 6, 12, and 24 months after surgery. The chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Where the Orbscan was applied to evaluate differences between pre-operative and postoperative posterior corneal elevation values, several cases of posterior corneal ectasia were detected. [15][16][17][18][19] On the other hand, the Pentacam revealed no significant changes in posterior elevation values, as is generally expected in keratorefractive surgery. 20,21 Additionally, the Orbscan II also exhibited low repeatability in the measurement of post-operative posterior corneal surface elevation.…”
Section: Corneal Elevationsupporting
confidence: 68%
See 1 more Smart Citation
“…Where the Orbscan was applied to evaluate differences between pre-operative and postoperative posterior corneal elevation values, several cases of posterior corneal ectasia were detected. [15][16][17][18][19] On the other hand, the Pentacam revealed no significant changes in posterior elevation values, as is generally expected in keratorefractive surgery. 20,21 Additionally, the Orbscan II also exhibited low repeatability in the measurement of post-operative posterior corneal surface elevation.…”
Section: Corneal Elevationsupporting
confidence: 68%
“…These findings are aligned with the results of some previous research work on the influence of keratorefractive surgery on the posterior corneal surface. Where the Orbscan was applied to evaluate differences between pre‐operative and post‐operative posterior corneal elevation values, several cases of posterior corneal ectasia were detected 15–19 . On the other hand, the Pentacam revealed no significant changes in posterior elevation values, as is generally expected in keratorefractive surgery 20,21 .…”
Section: Imaging Capabilitiesmentioning
confidence: 86%
“…Many previous studies have reported forward shift of posterior surface after keratorefractive surgery based on the Orbscan system (Kim et al. ; Lee et al. ; Martin & Rachidi ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies, using scanning slit‐beam corneal topography (Orbscan corneal topography), mostly reported a forward shift of the posterior corneal surface (Kim et al. ; Lee et al. ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation